Municipalities Cooperation – a case study Voitsberg - Zsilincsar, Walter (Journal for Geography, 2006)
Small-town-agglomerations like the one in Western Styria comprising five communities to form a “Kernraumallianz (core-area-alliance)” are a new and growing challenge for regional planners politicians, urban-, social-, and liberal trends in economy have brought about new problems for the communes which they themselves are no longer able to solve. An additional hardship is caused by the obligation to fulfil the rigid Maastricht – criteria facing shrinking communal incomes and rising expenditures. All that together with the necessity to create new jobs, to modernize and improve communal services, all in all to make the single community competitive in its struggle for survival has convinced communal politicians that cooperation with their neighbouring partners facing similar problems is probably the best way to find opt solutions. This way, however, turns out a very stony one, wherein reducing the financial burden is perhaps the biggest obstacle. The “Kernraumallianz” tries to overcome the communal crisis through cooperation on a free will basis. It should be mentioned in this context, however, that inter-communal cooperation in densely settled urban areas today is a necessity and demands new modes of administration since communal growth not only of the core-cities has transgressed administrational confines long ago.
Keywords: core-area-alliance; small-town-agglomeration; municipalities cooperation